Importance of high-quality evidence regarding the use of Bacopa monnieri in dementia - Agarwal, Ayush; Mishra, Biswamohan; Gupta, Anu; Srivastava, M. Vasantha Padma; Basheer, Aneesh; Sharma, Jyoti; Vishnu, Venugopalan Y. (Frontiers in Aging Neuroscience, 2023)
Abstract Background: Bacopa monnieri (BM), a commonly used herb, has shown neuroprotective effects in animal and in-vitro studies; but human studies on patients with Alzheimer’s Disease (AD) have been inconclusive. Further high-quality trials are required to conclusively state the utility of BM in AD and other neurodegenerative dementias Methods: In the present study, we did a narrative review of the current challenges in designing clinical trials of BM in dementia and their evidence-based recommendations Results: Many facets of the BM trials need improvement, especially effect size and sample size estimation. Current assessment and outcomes measures need a more holistic approach and newer scales for diagnosing and monitoring prodromal AD. The stringent guidelines in CONSORT and STROBE are often considered difficult to implement for clinical trials in ayurvedic medications like BM. However, adherence to these guidelines will undoubtedly improve the quality of evidence and go a long way in assessing whether BM is efficacious in treating AD/ prodromal AD patients and other neurodegenerative dementias. Conclusions: Future studies on BM should implement more randomized controlled trials with an appropriate sample size of accurately diagnosed AD/ prodromal AD patients, administering a recommended dosage of BM and for a pre-specified time calculated to achieve adequate power for the study. Researchers should also develop and validate more sensitive cognitive scales, especially for prodromal AD. BM should be evaluated in accordance with the same rigorous standards as conventional drugs to generate the best quality evidence.